Survey of Nutritional Status and Health Behavior of Pregnant Women in Bontomate'ne Health Center District Jeneponto - Yusriani, Yusriani (YCAB Publisher & IAKMI SULTRA, 2016)
Background: Maternal mortality is a global health problem, and generally occurs mainly in developing countries. The main causes of maternal mortality still include bleeding, eclampsia and infections which contribute about 60% of total maternal deaths. Interventions to reduce the number of maternal deaths is pretty much done, especially in improving the nutritional status and health behavior of pregnant women, but have not yielded optimal results.Aim: This study aimed to determine the nutritional status and health behavior of pregnant women at health centers Bontomate'ne Jeneponto.Methods: This study uses survey design analytic descriptive approach. The population was all pregnant women in the working area Bontomate'ne health center with 189 people. All the population census or taken by total sampling. Data obtained through direct interviews and observations by using a questionnaire.Results: The results showed that normal nutritional status of pregnant women as much as 85.1% and maternal nutritional status category KEK as much as 14.9%. Knowledge of pregnant women about the risk factors of maternal death, danger signs of pregnancy, the importance of antenatal care (ANC), planning a pregnancy and a safe delivery and post natal care (PNC) is categorized as less as much as 90.1%, and the mother's knowledge enough category only 9.9%. Pregnant women who have a positive attitude by 71.3% and amounted to 28.7% negative. Actions poor pregnant women as much as 34.7% and the capital measures both categories as much as 65.3%.Conclusion: Nutritional status and health behavior of pregnant mothers can provide chances for the occurrence of maternal deaths. Suggested the need to conduct needs to conduct education and training to build the knowledge and experience of pregnant women about the nutritional status and health behavior was good with involving the active participation of health workers, community, family, mother and husband.